Protective mechanisms of betablockers for coronary artery disease are by distal vasoconstriction and slower speed: a study by angiographic assessment and artificial intelligence program. (14th October 2021) - Duong, H; Nguyen, T; Ho, D; Le, M; Thai, M
Abstract: Background: Patients with coronary artery disease (CAD) were protected with betablockers (BB) for lower mortality and lower rate of new myocardial infarction. What are the protective mechanisms? In prior studies, our hypothesis was that damage to the intima of the coronary arteries was caused by cavitation or rupture of bubbles which was seen frequently in industrial pipes. The bubbles ruptured when they flew in areas of different pressures among the layers and segments of the coronary flows. How did BB change the dynamic of coronary flow? Methods: After percutaneous coronary interventions (PCI) patients were started on BB. Later, when there was indication, the patient underwent another angiogram. The diameter of the distal LAD was measured and compared between the two angiograms. The distance reached the coronary flow after 0.6seconds was calculated in both angiograms and compared. In the reviewing protocol, the coronary angiograms were done with the contrast injected until the index coronary artery was completely opacified. As the injection of contrast stopped, the blood in white color moved in and displaced the contrast in black color. The morphologies, movements, directions, and interactions of the blood flow in white color above a black background were reviewed frame by frame by investigators analyzing flow dynamics. At the same time, the artificial intelligence (AI) program has 2 models (build on Python), The model 1 was built based on U-net and Densenet-121 for vessel segmentation. Model 2 was used for classification of stagnant flow or normal, the model 2 was trained based on the convolutional neural network with the dataset selected from model 1 results. Results: In total, 50 patients were included with a total of 50 pairs of angiograms. In 80% patients, the diameter of the distal segment of the LAD was 20% smaller in BB compared with before BB (p≤0.05). In 75%, the speed of the coronary after BB was lower (p<0.05), A lower speed guaranteed laminar flow and less chance for cavitation. The above data was confirmed by the AI programs. Conclusion: BB improved the coronary flow by decreasing the diameter of the arteries so decreased the turbulent flow and promoted laminar flow. BB also decreased the speed of the flow so decreased the chance for cavitation. Both decreased the possibility of ACS. Funding Acknowledgement: Type of funding sources: None.